The Effect of Using English Podcast Towards Students’ Speaking Skills at Tenth Grade of MAN 2 Agam - Akbar, Adil Fadhillah; Reflinda, Reflinda; Melani, Melyann; Putri, Hilma Pami (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Digital recordings that include programmes from radio, television, and interviews are called podcasts. It is regarded as a useful instrument for teaching English abilities. The goal of this study was to use English podcasts in the teaching and learning process to enhance students' English-speaking abilities. This study employed an experimental design with a pretest-posttest control group setup. The experimental class, IPA 1, and the control class, IPA 2, were both selected. The test was offered as an oral examination. Following that, statistical methods were used to compute the data from the before and post testing. The outcome demonstrated that the experimental class's post-test score wasgreater than both its pre-test and post-test resultsof control class. The results revealed that after undergoing treatments, the students' speaking skills performance in the experimental class significantly improved. Speaking abilities in the experimental class were significantly different from those in the control class. It was also moreeffective to teach speaking skills with English podcasts than without them. Thus, English podcast is a media that can be a viable alternative for teaching English, particularly speaking in EFL classrooms.